Kryzys nowoczesnego konstytucjonalizmu. Między liberalną sędziokracją a postliberalnym populizmem - Sulikowski, Adam (Filozofia Publiczna i Edukacja Demokratyczna, 2018)
The author assumes that modern, Western constitutionalism, with its emphasis on individual rights, is not the only form of constitutionalism, understood as ideas of restrictions imposed on government activities, practiced throughout history. In the author’s opinion, the current crisis of the dominant paradigm of constitutionalism is caused by the contradictions of liberal democracy. In this aspect, the author’s analysis is based on the concepts of Antonio Gramsci, Chantal Mouffe, Ernesto Laclau and Claude Lefort. In the author’s opinion, the described crisis may lead to permanent transformations and the emergence of new forms and paradigms of constitutionalism.